Earth then and now - Quinn, Robert (New York: Oxford University Press, 2010)
This exciting new series of non-fiction readers provides interesting and educational content, with activities and project work. The readers are graded at four levels, from 3 to 6, suitable for students from age 8 and older. They can support Content and Language Integrated Learning (CLIL), andcover a broad range of topics, within three curriculum areas:The World of Science and TechnologyThe Natural WorldThe World of Arts and Social StudiesAlso available for each reader:Activity BookAudio CD Pack (Reader and Audio CD)Teacher's Notes and CLIL guidance at www.oup.com/elt/readanddiscover
Keywords: Earth sciences -- Juvenile literature; Earth (Planet) -- Juvenile literature; Literature